The Impact of Zakat on the - عبد السلام , عائشة (Dirasat in Economics and Business, 2015)
This study discusses the impact of zakat on the economic stability through its influence on consumption and investment. The impact of zakat on jobs, employment increment, income distribution fighting money stockpiling encouraging means of crediting and its effect on economic cycle were all discussed. The study found that zakat important economic tool to achieve the economic stability.